Nonocclusive mesenteric ischemia associated with a hyperosmolar hyperglycemic state: Hepatic portal venous gas as an indicator of mesenteric ischemia. Issue 1 (30th June 2021) - Takiguchi, Toru; Arai, Masatoku; Kim, Shiei; Ishii, Hiromoto; Ogasawara, Tomoko; Shigeta, Kenta; Mizobuchi, Taiki; Yokobori, Shoji
Abstract : Background: The diagnosis of nonocclusive mesenteric ischemia (NOMI) is always challenging in critically ill patients. Herein, we aimed to report a case of NOMI associated with a hyperosmolar hyperglycemic state (HHS). A small amount of hepatic portal venous gas (HPVG) triggered the diagnosis of NOMI. Case Presentation: A 77‐year‐old man was transferred due to shock and disorder of consciousness. He was diagnosed with an HHS. We suspected intestinal ischemia due to a small amount of HPVG revealed by computed tomography (CT). Peritoneal signs were revealed after treatment for the HHS. Computed tomography was carried out again 5 h after admission, which showed a large amount of HPVG, remarkable bowel dilatation, and pneumatosis intestinalis. We performed an emergency laparotomy and resected the small bowel necrosis resulting from NOMI. Conclusion: An HHS can cause NOMI, and the presence of HPVG on CT is an important finding that suggests mesenteric ischemia, even in small amounts. Abstract : The diagnosis of nonocclusive mesenteric ischemia (NOMI) is always challenging in critically ill patients. We reported a case of NOMI associated with a hyperosmolar hyperglycemic state. A small amount of hepatic portal venous gas triggered the diagnosis of NOMI.